Time correlation of success recanalization for endovascular recanalization of medically refractory non-acute intracranial arterial occlusions - Ji, Zhiyong; Ling, Yeping; Chen, Pingbo; Meng, Yuxiao; Xu, Shancai; Wu, Pei; Wang, Chunlei; Ilyasova, Tatiana; Sun, Bowen; Shi, Huaizhang (Frontiers in Surgery, 2023)
Background and purpose The management of patients with symptomatic non-acute atherosclerotic intracranial artery occlusion (sNAA-ICAO), which is a special subset with high morbidity and a high probability of recurrent serious ischemic events despite standard medical therapy, has been clinically challenging. A number of small-sample clinical studies have discussed endovascular recanalization for sNAA-ICAO and the lack of a uniform standard of operation time. The purpose of this study was to investigate the time correlation of successful recanalization. Methods From January 2013 to August 2021, 69 consecutive patients who underwent endovascular recanalization for sNAA-ICAO were analyzed retrospectively in the First Affiliated Hospital of Harbin Medical University. The technical success rate, periprocedural complications, and rate of TIA/ischemic stroke during follow-up were evaluated. Results The overall technical success rate was 73.91% (51/69), and the rate of perioperative complications was 37.68% (26/69). The percentage of patients with perioperative symptoms was 27.53% (19/69). The rate of serious symptomatic perioperative complications was 8.70% (6/69). After adjusting for age, sex, and BMI, the effect of the time from the last symptom to operation on successful recanalization was 0.42 (IQR, 0.20, 0.88, P = 0.021), before the inflection point (51 days). Conclusions Endovascular recanalization for sNAA-ICAO is technically feasible in reasonably selected patients. The perioperative safety is within the acceptable range. Before 51 days, the last symptoms to operation time, for every 10 days of delay, the probability of successful recanalization is reduced by 57%.